Rehabilitation after amputation of the lower limb in the course of Diabetic Foot Syndrome - Karpińska, Anna; Karpińska, Ewa Małgorzata; Klich-Kufel, Maria (Journal of Education, Health and Sport, 2019)
One of the most popular civilization diseases is type II diabetes. Abnormal glucose metabolism leads to life-threatening complications within the nervous and vascular systems. Irregularities of these systems in case of some patients lead to the development of the Diabetic Foot Syndrome. The resulting imprints, wounds, abrasions and calluses are a good environment for the development of bacteria, which is why there is a high risk of wound infection leading to the appearance of a difficult to heal ulcer. In life-threatening conditions, doctors decide to amputate the limb. In order to regain dexperity and independence, the patient after the limb amputation should start rehabilitation as soon as possible.